Kerapatan Qadi: Exploration of the Implementation of Islamic Law in Kalimantan - Sabarudin Ahmad; Lisnawati Lisnawati; Muhammad Riyas Rasyid; Muhammad Gesit Widayatno (Syariah: Jurnal Hukum dan Pemikiran, 2026)
The Kerapatan Qadi is a judicial institution during the Banjar Kingdom era. This institution not only served as a place for those seeking justice but also symbolized the implementation of Islamic law in Kalimantan. The purpose of this study is to analyze and explore the Kerapatan Qadi as a manifestation of the enforcement of Islamic law in Kalimantan. This research falls under the category of empirical legal research using a historical approach. The data sources for this research can be classified into three categories: primary, secondary, and tertiary data, which are then analyzed using the theories of living law and the applicability of law. The results of this study indicate that, first, the Kerapatan Qadi as a judicial institution has existed since the establishment of the Banjar Kingdom in Kalimantan, and during the Dutch colonial era, it received legitimacy through Stbl. 1937 No. 116 and 610 regarding Religious Courts in Java and Madura, which confirmed Stbl. 1882 No. 152, as well as Stbl. 1937 Nos. 638 and 639 regarding the establishment of judicial institutions for South and East Kalimantan. The Kerapatan Qadi in Kalimantan is divided into two levels. The First-Level Kerapatan Qadi was spread across several important regions, including Negara, Kandangan, Barabai, Amuntai, Tanjung, Rantau, Pelaihari, Martapura, Banjarmasin, and Marabahan. Meanwhile, the Appellate level was held at the Kerapatan Qadi Besar in Banjarmasin. Second, the enforcement of Islamic law in Kalimantan, particularly during the Banjar Sultanate era, can be observed from the existence of the Kerapatan Qadi as an official judicial institution that upheld Islamic law. This study examines the rulings issued by the Kerapatan Qadi and demonstrates that the institution had broad jurisdiction, covering family law (ahwal syakhshiyah), criminal law (jinayah), and issuing fatwas.